2007
DOI: 10.1007/s00535-006-1978-8
|View full text |Cite
|
Sign up to set email alerts
|

Mental status impairment in patients with West Haven grade zero hepatic encephalopathy: the role of HCV infection

Abstract: The investigation of patients with cirrhosis by the West Haven test is not sufficient to identify subclinical forms of encephalopathy. The Trail Making Test (a simple, inexpensive test) in our series evidenced poor psychometric performance in more than half of the patients who were free of manifest encephalopathy. Subclinical hepatic encephalopathy was present mostly in patients with HCV-related cirrhosis. Detecting minimal hepatic encephalopathy in patients with cirrhosis may help improve their quality of lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…When applying PREPs, which are in fact vertex responses, in a clinical setting, some authors fail to discuss the possible role of cognitive factors influencing the vertex response. In HCV patients, an early significant impairment of higher cognitive function has been demonstrated and its role in producing PREP abnormalities cannot be excluded [6]. Regarding these possible limitations of vertex potentials for analysing peripheral pathways, the investigations of Rossi et al [28] are of outstanding importance to the validation of our study.…”
Section: Discussionmentioning
confidence: 96%
“…When applying PREPs, which are in fact vertex responses, in a clinical setting, some authors fail to discuss the possible role of cognitive factors influencing the vertex response. In HCV patients, an early significant impairment of higher cognitive function has been demonstrated and its role in producing PREP abnormalities cannot be excluded [6]. Regarding these possible limitations of vertex potentials for analysing peripheral pathways, the investigations of Rossi et al [28] are of outstanding importance to the validation of our study.…”
Section: Discussionmentioning
confidence: 96%
“…Patients with specific etiologies of cirrhosis are more likely to exhibit psychometric impairment, specifically chronic hepatitis C. Investigations in the chronic hepatitis C infected groups (both with and without cirrhosis) show a worse psychometric performance compared to patients without chronic hepatitis C in selected studies [30][31][32][33] . However, other studies have not demonstrated a difference in psychometric performance of cirrhotics with chronic hepatitis C compared to those without it [30,34] .…”
Section: Contribution Of Concomitant Diseases To Mhementioning
confidence: 99%
“…The most widely used method of grading HE is the West Haven Criteria (WHC) [ 24,25 ] , which is determined by clinical examination and based on the subjective evaluation of the clinician (see Table 29.2 ). This method has been criticized for lack of sensitivity to detect subtle brain dysfunction [ 26 ] . Neuropsychological or neurophysiological measures are recommended to identify less severe stages of HE [ 7,27 ] .…”
Section: Classi Fi Cation and Grading Of Hementioning
confidence: 99%